1991
DOI: 10.1159/000457501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Phototherapy Lights on Retinal and Choroidal Blood Flow

Abstract: The response of retinal (RBF) and choroidal (ChBF) blood flow to illumination with light with different spectra was investigated in spontaneously breathing newborn piglets. After 1 h in complete darkness, the animals were exposed to blue, white or green light in such a manner that equal energy was delivered to the eye. RBF and ChBF showed different flow responses. After 60 min exposure to blue light, RBF increased from 0.22 ± 0.01 ml/min/g at baseline to 0.32 ± 0.03 ml/min/g (± SEM) (p < 0.03). Apart from this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(24 reference statements)
0
5
0
1
Order By: Relevance
“…Note that the absence of labeled neurons in EW in the cases reported here with PRV injections confined or largely confined to choroid suggests that, unlike in birds (Reiner et al, 1983 , 1991 ; Cuthbertson et al, 1996 ), the EW-ciliary ganglion circuit in rats does not exert a major direct influence on control of ChBF. As this circuit in birds receives input from the suprachiasmatic nucleus (SCN), which also was not labeled in our 8 choroidal cases, and is responsible for light-mediated control of ChBF in birds (Fitzgerald et al, 1996 ; Shih et al, 1997 ), the light-mediated regulation of ChBF reported in piglets, monkeys and humans does not appear to be mediated by either SCN or EW in mammals (Parver et al, 1982 , 1983 ; Bill and Sperber, 1990 ; Stiris et al, 1991 ; Longo et al, 2000 ). In this regard, the PRV+ neurons in the ventrocaudal part of the spinal trigeminal nucleus are of interest.…”
Section: Discussionmentioning
confidence: 69%
“…Note that the absence of labeled neurons in EW in the cases reported here with PRV injections confined or largely confined to choroid suggests that, unlike in birds (Reiner et al, 1983 , 1991 ; Cuthbertson et al, 1996 ), the EW-ciliary ganglion circuit in rats does not exert a major direct influence on control of ChBF. As this circuit in birds receives input from the suprachiasmatic nucleus (SCN), which also was not labeled in our 8 choroidal cases, and is responsible for light-mediated control of ChBF in birds (Fitzgerald et al, 1996 ; Shih et al, 1997 ), the light-mediated regulation of ChBF reported in piglets, monkeys and humans does not appear to be mediated by either SCN or EW in mammals (Parver et al, 1982 , 1983 ; Bill and Sperber, 1990 ; Stiris et al, 1991 ; Longo et al, 2000 ). In this regard, the PRV+ neurons in the ventrocaudal part of the spinal trigeminal nucleus are of interest.…”
Section: Discussionmentioning
confidence: 69%
“…It may thus be that a corneal response to bright light, which appears to be mediated via an innervation from melanopsin-containing trigeminal fibers (Matynia et al, 2016), can drive ChBF increases via a projection from cornea-responsive trigeminal nucleus neurons to the choroidal SSN. Finally, while light-mediated increases in ChBF have been demonstrated in many studies in mammals, light-mediated ChBF increases have not been observed in some studies in rabbits and newborn piglets (Stjernschantz et al, 1977; Stiris et al, 1991), nor were ChBF increases in response to diffuse luminance flicker observed in cats (Riva et al, 1994), and only small, non-statistically significant increases were seen in a study in humans (Garhöfer et al, 2002).…”
Section: Facial Nucleus Parasympathetic Input To Choroidmentioning
confidence: 89%
“…Thus, unlike in birds (Reiner et al, 1983, 1991; Cuthbertson et al, 1996), the EW-ciliary ganglion circuit in rats does not appear to exert a direct influence on ChBF. This raises the possibility that the light-mediated regulation of ChBF reported in various mammalian species (Parver et al, 1982, 1983; Bill and Sperber, 1990; Stiris et al, 1991; Longo et al, 2000) is not mediated by either SCN or EW.…”
Section: Facial Nucleus Parasympathetic Input To Choroidmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the retinal circulation in mammals is under autoregulatory control by local tissue metabolic demands. As a consequence, retinal flow is responsive to illumination conditions, since these affect retinal activity and thereby local tissue metabolic requirements (Bill & Sperber, 1990;Stiris et al, 1991;Feke et al, 1983;Riva et al, 1983).…”
Section: Retinal Versus Choroidal Circulationsmentioning
confidence: 99%